OVERCOMING THE POVERTY TRAP THROUGH EDUCATION: AN INTERGENERATIONAL STUDY ON INDONESIA - Pohan, Hilda L. Masniarita; Vitale, Jefrey D. (Journal of Indonesian Applied Economics, 2016)
Poverty has an inter-generational dimension. Individuals born into poor families are constrained to obtain education. Low education leads to low productivity which then leads to low income. The purpose of this study is to present a case study of Indonesia’s experience with public expenditures on education and its effect on inter-generational poverty alleviation and medium term impact on individual income. This study uses Indonesian Family Life Survey (IFLS) data consisting of families’ income, level of education, and health data over a ten year period. The results suggest that education explains the income variation. Parents’ income plays a bigger role in predicting children’s income than parents’ income. It suggests the importance of education in breaking the inter-generational poverty trap.